2022
DOI: 10.3390/min12020185
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Numerical Analysis of Deformation and Failure Characteristics of Deep Roadway in Coal Mines: A Case Study

Abstract: With the development of deep, underground coal mines in China, the failure mechanism of the rocks surrounding roadways is becoming increasingly complicated and the deformational control is also significantly difficult. In this study, based on the temporal and spatial deformational distribution of the deep roadway area in the 2233 working face of Fuxin Hengda Coal Mine, factors affecting the deformation and failure mechanism of deep-buried roadways, such as cohesion (c), tensile strength (), internal friction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…The evaluation of surrounding rock support effect is a comprehensive evaluation of multi-factor indicators, therefore a three-layer data model is constructed based on the above orthogonal experimental data 32 . The anchor cable prestress, length and spacing are used as the factor layers, and the top plate, the deformation of the two sides and the volume of the plastic zone are used as www.nature.com/scientificreports/ the test evaluation index layers, as shown in Table 6.…”
Section: Support Optimization Orthogonal Matrix Analysismentioning
confidence: 99%
“…The evaluation of surrounding rock support effect is a comprehensive evaluation of multi-factor indicators, therefore a three-layer data model is constructed based on the above orthogonal experimental data 32 . The anchor cable prestress, length and spacing are used as the factor layers, and the top plate, the deformation of the two sides and the volume of the plastic zone are used as www.nature.com/scientificreports/ the test evaluation index layers, as shown in Table 6.…”
Section: Support Optimization Orthogonal Matrix Analysismentioning
confidence: 99%
“…The orthogonal design experiment method is a mathematical-statistical method suitable for multi-factor experiments 45 . In order to explore the failure and deformation of the roadway under the dynamic disturbance condition under the multi-factor condition, the orthogonal experiment method is adopted.…”
Section: Numerical Simulation Of Roadway Deformation and Failure Unde...mentioning
confidence: 99%
“…In simulation, using PFC 2D software, the results indicated that increasing water content within the rock significantly decreased the coal strength, strain ratio (strain to peak strain), Young's modulus, AE energy (average), and the maximum energy of a single AE event. Some researchers used strain energy density for fracture predictions [44][45][46][47]. Lin et al studied the AE parameters during disccutter-induced rock fragmentation processes under various water conditions [48].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars studied the evolution of microcracks in rocks under saturated conditions using AE data [49]. The results demonstrated that the varying characteristics of rock crack propagation could be characterized by the AE events frequency along with volume change [12,28,46,50].The change in P-wave velocity along with AE parameters in porous rock were studied after micro-crack closure by Fortin et al and Liu et al [51,52]. Zhou et al have taken sandstone under different water contents as a research object and investigated AE characteristics along with the type I fracture mechanism [53].…”
Section: Introductionmentioning
confidence: 99%